Biology of VO2max: looking under the physiology lamp. (25th November 2016) - Lundby, C.; Montero, D.; Joyner, M.
Abstract: In this review, we argue that several key features of maximal oxygen uptake (VO2 max) should underpin discussions about the biological and reductionist determinants of its interindividual variability: (i) training‐induced increases in VO2 max are largely facilitated by expansion of red blood cell volume and an associated improvement in stroke volume, which also adapts independent of changes in red blood cell volume. These general concepts are also informed by cross‐sectional studies in athletes that have very high values for VO2 max. Therefore, (ii) variations in VO2 max improvements with exercise training are also likely related to variations in these physiological determinants. (iii) All previously untrained individuals will respond to endurance exercise training in terms of improvements in VO2 max provided the stimulus exceeds a certain volume and/or intensity. Thus, genetic analysis and/or reductionist studies performed to understand or predict such variations might focus specifically on DNA variants or other molecular phenomena of relevance to these physiological pathways.